Using Autopsy Brain Tissue to Study Alcohol‐Related Brain Damage in the Genomic Age. (27th August 2013) - Sutherland, Greg T.; Sheedy, Donna; Kril, Jillian J.
<x xml:space="preserve">Abstract</x> The New South Wales Tissue Resource Centre at the University of Sydney, Australia, is one of the few human brain banks dedicated to the study of the effects of chronic alcoholism. The bank was affiliated in 1994 as a member of the National Network of Brain Banks and also focuses on schizophrenia and healthy control tissue. Alcohol abuse is a major problem worldwide, manifesting in such conditions as fetal alcohol syndrome, adolescent binge drinking, alcohol dependency, and alcoholic neurodegeneration. The latter is also referred to as alcohol‐related brain damage (ARBD). The study of postmortem brain tissue is ideally suited to determining the effects of long‐term alcohol abuse, but it also makes an important contribution to understanding pathogenesis across the spectrum of alcohol misuse disorders and potentially other neurodegenerative diseases. Tissue from the bank has contributed to 330 peer‐reviewed journal articles including 120 related to alcohol research. Using the results of these articles, this review chronicles advances in alcohol‐related brain research since 2003, the so‐called genomic age. In particular, it concentrates on transcriptomic approaches to the pathogenesis of ARBD and builds on earlier reviews of structural changes (Harper et al. Prog Neuropsychopharmacol Biol Psychiatry 2003;27:951) and proteomics (Matsumoto et al. Expert Rev Proteomics 2007;4:539).